Integrated Motion Planning and Coordination for Industrial Vehicles - Cirillo, Marcello; Pecora, Federico; Andreasson, Henrik; Uras, Tansel; Koenig, Sven (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
A growing interest in the industrial sector for autonomous ground vehicles has prompted significant investment in fleet management systems. Such systems need to accommodate on-line externally imposed temporal and spatial requirements, and to adhere to them even in the presence of contingencies. Moreover, a fleet management system should ensure correctness, i.e., refuse to commit to requirements that cannot be satisfied. We present an approach to obtain sets of alternative execution patterns (called trajectory envelopes) which provide these guarantees. The approach relies on a constraint-based representation shared among multiple solvers, each of which progressively refines trajectory envelopes following a least commitment principle.